Exploring the Effectiveness of Merdeka Belajar Kampus Merdeka Policy in Indonesian Higher Education Institutions: An In-depth Case Study Analysis - Sahya Anggara (STAI Hubbulwathan Duri, 2023)
The Merdeka Belajar Kampus Merdeka (MBKM) policy was introduced in 2019 as a major initiation in reforming the Indonesian higher education system. This policy aims to promote the autonomy and innovation of higher education institutions, as well as to improve the quality of education and graduates' skills. This study aims to explore the effectiveness of MBKM policy implementation in Indonesian higher education institutions through an in-depth case study analysis. The study uses a qualitative approach, with data collection techniques through interviews with key stakeholders in two Indonesian universities. The findings revealed that the implementation of the MBKM policy has had a significant impact on the autonomy and innovation of the universities. However, the policy's impact on the quality of education and graduates' skills is still uncertain, as the policy is relatively new, and further research is needed. The study concludes with recommendations for policymakers and university leaders to improve the effectiveness of the MBKM policy.